1985
DOI: 10.1055/s-2007-1017362
|View full text |Cite
|
Sign up to set email alerts
|

Transport Systems and Enzymes Involved in the Metamorphosis of Tryptophan into Serotonin

Abstract: Tryptophan (Trp), as the precursor of serotonin, has been introduced in the treatment of depression and isomnia, but its clinical effectiveness must be considered with caution. In this presentation, the different aspects concerning the transport of Trp from the intestine to the brain and its enzymatic conversion into serotonin are discussed. The study of recent literature shows that the discussion about the relative importance of free and total plasma Trp and of the competitive large neutral amino acids for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Also important in the function of the serotonergic system, the essential amino acid tryptophan is the precursor for serotonin synthesis (Baumann 1985). Several studies have demonstrated that plasma tryptophan levels are abnormally reduced in depressed subjects as compared to healthy controls (reviewed in (Ressler and Nemeroff 2000)); this effect is not evident in currently remitted subjects with major depressive disorder (RMDD) (Neumeister et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Also important in the function of the serotonergic system, the essential amino acid tryptophan is the precursor for serotonin synthesis (Baumann 1985). Several studies have demonstrated that plasma tryptophan levels are abnormally reduced in depressed subjects as compared to healthy controls (reviewed in (Ressler and Nemeroff 2000)); this effect is not evident in currently remitted subjects with major depressive disorder (RMDD) (Neumeister et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence have revealed that these two monoamines share the common enzymes for their biosynthesis and metabolism (Baumann, 1985;Cooper etal., 1991), and thereby modulate their functions each other. Sumi et al (1990) demonstrated that the recombinant human aromatic L-amino acid decarboxylase [EC4.1.1.28, AADC-] expressed in COS cells could catalyze decarboxylation of both L-DOPA and 5-HTP.…”
Section: Introductionmentioning
confidence: 99%